Nasal mask versus conventional oxygen supply for endoscopy under intravenous sedation: protocol for a systematic review and meta-analysis - Jun Lu; Bo Li; Min Zheng; Yu Deng; Lulong Bo; Wentao JI; Xiaoting Zhang; Jinhai Liu (BMJ Open)
Introduction Hypoxaemia is a frequent complication associated with endoscopy conducted under intravenous sedation, highlighting the need for effective and practical interventions. This systematic review aims to evaluate the effectiveness of nasal mask oxygenation in reducing the incidence of hypoxaemia during endoscopy under intravenous sedation compared with the conventional oxygen supply.Methods and analysis This study strictly adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocol guidelines. PubMed, Embase, Cochrane Library, Web of Science and China National Knowledge Infrastructure databases will be electronically searched from their inception to May 2024 to identify randomised controlled trials comparing a nasal mask with conventional oxygen supply for endoscopy under intravenous sedation. The study selection, data extraction and quality assessment processes will be conducted independently by two reviewers. The risk of bias in the included studies will be assessed using the Cochrane Risk of Bias Tool for Randomized Trials, and the strength of evidence will be assessed using the Grading of Recommendations Assessment, Development, and Evaluation guidelines. The meta-analysis will be performed using STATA V.16.0, with effect sizes calculated using the standardised mean difference and 95% CI. Heterogeneity will be assessed using Cochran’s Q statistics, and inconsistency will be measured using I2 statistics. Potential sources of bias will also be evaluated.Ethics and dissemination The data used for this systematic review will be exclusively extracted from published studies. Additional ethical approval and informed consent are not required. This systematic review will be published in a peer-reviewed journal and will be presented at conferences and congresses.PROSPERO registration number CRD42024545231